2017
DOI: 10.1177/0885328217728448
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatibility and biologic characteristics of synthetic scaffold materials of rabbit acellular vascular matrix combining with human-like collagen I

Abstract: Scaffold material provides a three-dimensional growing environment for seed cells in the research field of tissue engineering. In the present study, rabbit arterial blood vessel cells were chemically removed with trypsin and Triton X-100 to prepare rabbit acellular vascular matrix scaffold material. Observation by He&Masson staining revealed that no cellular components or nuclei existed in the vascular intima and media after decellularization. Human-like collagen I was combined with acellular vascular matrix b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…There are a lot of evidences to prove that the PI3K/Akt cascade participates in many cell functions including metabolism, proliferation, or growth 1,14. Therefore, the dysregulation of this cascade can lead to a variety of conditions, including cancer, diabetes, and neurologic diseases 17,25. Findings of the present study are consistent with the previous studies, which reported that the inhibition of PI3K dramatically alleviates inflammatory and neuropathic pain 19,20,30.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There are a lot of evidences to prove that the PI3K/Akt cascade participates in many cell functions including metabolism, proliferation, or growth 1,14. Therefore, the dysregulation of this cascade can lead to a variety of conditions, including cancer, diabetes, and neurologic diseases 17,25. Findings of the present study are consistent with the previous studies, which reported that the inhibition of PI3K dramatically alleviates inflammatory and neuropathic pain 19,20,30.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that RES relieves neuropathic pain through the activation of spinal SIRT1 34. The phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) pathway is one of the most important participants in modulating nociceptive information and is centrally sensitized in the microglial intracellular signaling cascades 25. RES has been found to protect neuronal cells from oxidative cytotoxicity via PI3K/Akt pathway 24.…”
Section: Introductionmentioning
confidence: 99%
“…ACVM-0.25% -HLC-I scaffold is a tissue engineering composite scaffold material, which has the advantages of natural biological scaffold material and synthetic biodegradable polymer scaffold material. In other words, it provides three-dimensional structural space for cell growth and has certain biomechanical properties [14,16]. Our previous study [16] has demonstrated that ACVM-0.25% HLC-I has good compatibility with cells, low cytotoxicity, can promote cell adhesion, cell proliferation and cell migration, and has sufficient mechanical properties to maintain the tensile strength of the material.…”
Section: Discussionmentioning
confidence: 99%
“…An ACVM-0.25% HLC-I scaffold was prepared on the basis of previous studies [14,15]. The third-generation of HGFs with good growth condition was collected, digested at 0.25% trypsin (Sigma Biotechnology) 37 C for 5 min, and then centrifuged at 1000 rpm/min to remove supernatant and adjust cell concentration to 1 Â 10 6 cells/mL.…”
Section: Preparation Of Hgecs-hgfs-vecs-acvm-025% Hlc-i Composite Scmentioning
confidence: 99%
See 1 more Smart Citation